The impact of unskilled immigration on local labour markets - Benjamin Weigert; Christian Lumpe (Verein für Socialpolitik, 2010)
In a search-theoretic two region model, we analyse the impact of unskilled immigration and skill biased technological change on native wages and unemployment in local labour markets. We show that a specific combination of number and skills of immigrants generates a technology adoption of firms leading to insignificant wage changes. Thus our models explains the observed phenomenon of skill biased technological change, wage inequality and high inflows of immigrants in local labour markets. Our analysis also considers possible compensating or magnifying effects of native out-migration.
Keywords: F22; J31; J60; 330; search theory; immigration; wage inequality